Structural changes in the agricultural landscape and occurence of gene pool importance trees - Supuka, Ján; Pucherová, Zuzana (Folia oecologica, 2013)
The content of this paper is assessment of the changes in the landscape structure in the cadastral area in Zirany as compared between 1869 and 2012. In the second part of this paper, the occurrence of gene pool trees identified within the cadastral area is presented. Changes in the representation of landscape elements, their internal structure and surface-area spatial distribution of land is a reflection of property ownership relations, land use forms, especially forms of intensification in agriculture and socio-economic development of society. Landscape structure was evaluated from maps and field research of the current situation. The current landscape structure (CLS) in 2012 was evaluated using 9 groups and a total of 44 landscape elements. In assessing the historical landscape structure (HLS) from 1869, 8 groups and 19 basic landscape elements were used. The most significant changes in the secondary landscape structure between 1869 and 2012 were identified in the following elements in the compared time periods: a slight decrease in the portion of forest (from 42.83 to 40.76%), increase in the portion of nonforest woody vegetation (from 0.33 to 4.00%), reducing the share of agricultural used areas (from 44.16 to 37.86%), decrease of surface of grass-herb vegetation (from 10.17 to 5.99%) and increase of the built up areas (from 1.56 to 6.44%). A significant change is observed in the conversion of mosaic structure of narrow-band fields to large-block forms of agricultural land use. Attention was devoted on the spatial distribution of tree species and biodiversity in the group of non-forest woody vegetation (NFWV) during the mapping of the CLS features. In the formations of NFWV 6 species with important gene pool and above-standard biometry and age of trees have been identified with a total of 47 subjects within the land. These are the species: Castanea sativa Mill. (18 subjects) Mespilus germanica L. (1 subject), Quercus cerris L. (1 subject), Q. dalechampii Ten. (2 subjects), Q. petraea (Mattusch.) Liebl. (23 subjects), Q. polycarpa Shur. (2 subjects). Genetically significant trees were also localized by GPS. [PUBLICATION ABSTRACT]